(untitled) (Scientific journal of the Fergana State University, 2023)
During the practical experiments of this study, a modified polyethylene composite was obtained by introducing 5% aluminum acetate salt into the polyethylene macromolecule. The thermal decomposition of this obtained composite was investigated in order to study the high temperature resistant property. Based on the results of the analysis, a technical conclusion was obtained on the results of the TGA and DTA curves of the composite.